Keamanan Konsumen dalam Penggunaan Nomor Telepon Daur Ulang: Tinjauan Hukum Perlindungan Konsumen - Dwiputri, Ayunda Rahmayanti; Farina, Thea; Ali, Nuraliah (Palangka Law Review, 2024)
This study examines legal issues related to the recycling system of mobile phone numbers implemented by telecommunications service providers, which has the potential to harm consumers. The primary issue is the violation of consumer rights under Law Number 8 of 1999 concerning Consumer Protection, particularly regarding the incomplete deletion of the previous owner's personal data during the number recycling process. The aim of this research is to analyze the impact of the implementation of the mobile phone number recycling system on consumers and to assess the extent to which this system fails to comply with the Consumer Protection Law, resulting in losses for consumers, especially concerning privacy and data security. This study employs a normative juridical method, utilizing an analytical approach to legislation, with a focus on the Consumer Protection Law. The research also includes case studies related to consumer rights violations resulting from the inadequacies of the mobile phone number recycling system. The research findings indicate that the recycling system for mobile phone numbers has not been implemented in accordance with applicable regulations. Personal data from previous number owners is not completely deleted, allowing such data to remain accessible to the new users. As a result, new consumers face significant privacy risks, such as the potential misuse of their data. This situation leads to both material and immaterial losses for consumers, particularly in terms of security and comfort in using telecommunication services.